Recurrent Left Ventricular Pseudoaneurysm: Diagnosed by Color-Flow Doppler Echocardiography - Gaos, Carlos M. (1990)
The effects of left ventricular pseudoaneurysm following transmural myocardial infarction can be devastating; therefore, prompt diagnosis and surgical resection are warranted. We report a rare case of recurrent left ventricular pseudoaneurysm in which color-flow Doppler echocardiography was useful in establishing the diagnosis. (Texas Heart Institute Journal 1990;17:190-1)